Mapping of organizational maturity levels in the use of competitive intelligence: a survey on the 500 largest companies based on Brazil - Ciupak Bocardi, Clebia; Rodrigues, Leonel Cezar; Alves Silvente, Giseli (Journal of Sustainable Competitive Intelligence, 2022)
Objective: To map the Organizational Maturity Levels using Competitive Intelligence (CI) in the 500 largest companies headquartered in Brazil, using the classification proposed in the Rodrigues and Riccardi Model (2007) as a parameter. Methodology: The companies selected for this research are those elected by Exame Magazine as the Biggest and Best in 2016. For the characterization of the presence of Competitive Intelligence in companies, descriptive statistics were used, having as a data collection instrument the questionnaire developed by Puzzle. Originality: The recognition of the specialized literature on the criticality of CI systems for business success recognizes, if not a dichotomy (importance versus thematic unexplored), at least a clear void in the exploration of this topic, which constitutes a scientific gap that passes to be the object of this research. Results: The main results indicate that CI evolved from almost informality to higher levels of maturity, evidenced by the expansion of its functional activities, greater institutional coverage and greater formalization of its procedures. Theoretical/methodological contributions: This allows us to conclude that CI has increased its level of maturity in use in the companies surveyed, reaching levels 3 and 4 of maturity. The greater formalization of its processes and the extension of its reach give it institutional breadth and a more corporately useful and competitively strategic role.